+0  
 
0
203
1
avatar

3x- 7x2 - 7x + 3 = 0

Guest Jun 1, 2017
 #1
avatar
0

Solve for x:
3 x^3 - 7 x^2 - 7 x + 3 = 0

The left hand side factors into a product with three terms:
(x - 3) (x + 1) (3 x - 1) = 0

Split into three equations:
x - 3 = 0 or x + 1 = 0 or 3 x - 1 = 0

Add 3 to both sides:
x = 3 or x + 1 = 0 or 3 x - 1 = 0

Subtract 1 from both sides:
x = 3 or x = -1 or 3 x - 1 = 0

Add 1 to both sides:
x = 3 or x = -1 or 3 x = 1

Divide both sides by 3:
Answer: | x = 3          or x = -1            or x = 1/3

Guest Jun 1, 2017

31 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.